Sectoral Interdependencies and Multipliers in Nigeria: An Input-Output Approach - Effiong Mfonobong Okokon; Hosu Yiseyon Sunday (Journal of Global Innovations in Agricultural Sciences)
This study examines the sectoral contributions to Nigeria's Gross Domestic Product (GDP) and intersectoral interdependencies using Input-Output (I-O) analysis. Results as obtained from the 2022 Eurostat database revealed significant value added/sectoral contributions, agriculture ($6.512B, 15.1%), fishing ($4.529B, 1.1%), food/beverages ($8.446B, 19.6%), and mining/quarrying ($14.659B, 34.1%). Intersectoral interdependencies highlighted key intersectoral linkages between agriculture and food/beverages, mining/quarrying and other industries, and fishing and food/beverages. Results showed that agriculture's output (74.58%) is primarily consumed by households and used by the food and beverages sector; output from mining/quarrying (85.73%) is consumed mainly by industries (manufacturing/construction), and output from the fishing (81.68%) sector is mainly consumed by households and used by the food and beverages sector. The Type I and Type II multipliers assessed the economic ripple effects of changes in industry demand. The findings indicate substantial indirect effects, with output multipliers ranging from 1.726% (food/beverages), 2.118% (fishing), 1.803% (mining/quarrying), and 1.758% (agriculture). Income multipliers range from income multipliers: to $2.053B (food/beverages), $3.290B (fishing), $2.540B (agriculture), and $3.01B (mining/quarrying). Fishing and mining/quarrying sectors exhibited the highest total multiplier effects, emphasizing their potential for driving economic growth. The study confirms the robustness of the results using I-O analysis, validating the initial findings. Policy implications include targeted investments in strategic sectors such as agriculture, fishing, food/beverages, and mining/quarrying, which would stimulate economic growth and diversification. Also, resource allocation and diversification strategies to enhance intersectoral linkages would maximize economic benefits and reduce dependence on individual sectors.